Selective immunoglobulin A deficiency combined with juvenile idiopathic arthritis: a report of two cases and literature review - Tan Yinli; Buweimaieryemu Yusufu; Caiju Luo; Yikun Mou; Yuxing Zhu; Cai Yun (Egyptian Rheumatology and Rehabilitation)
Abstract Objective To investigate the clinical characteristics of selective immunoglobulin A deficiency (SIgAD) combined with juvenile idiopathic arthritis (JIA). Methods A retrospective analysis of the clinical data and follow-up data of children with SIgAD combined with JIA was conducted. Results Both patients were female, patient 1 was 13 years old and of Han nationality from Guangdong Province (southern China), and patient 2 was 4 years and 10 months old and of Uygur nationality from Xinjiang Province (northwest China). The main clinical manifestations were joint deformity, joint pain, limited activity, and a serum IgA concentration < 0 g/ L. After treatment with immunosuppressants, biological agents and rehabilitation, the symptoms improved, but joint deformity and functional disability remained. Conclusion Children with SIgAD combined with JIA may experience early disease onset, multiple joint involvement, and poor curative effects. Early diagnosis, timely intervention, and combination therapy are crucial for reducing long-term sequelae and improving clinical outcomes.